2012
DOI: 10.1111/j.1742-4658.2012.08712.x
|View full text |Cite
|
Sign up to set email alerts
|

HuPho: the human phosphatase portal

Abstract: Phosphatases and kinases contribute to the regulation of protein phosphorylation homeostasis in the cell. Phosphorylation is a key post-translational modification underlying the regulation of many cellular processes. Thus, a comprehensive picture of phosphatase function and the identification of their target substrates would aid a systematic approach to a mechanistic description of cell signalling. Here we present a website designed to facilitate the retrieval of information about human protein phosphatases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
1
49
0
1
Order By: Relevance
“…Phosphatase-substrate interaction is weak and transient, thus it is unlikely that substrates can be identified by co-immunoprecipitation. In fact none of the interactors identified in the affinity purification experiments are among the validated substrates annotated in the HUPHO and DEPOD databases (Li et al, 2013; Liberti et al, 2013). It has been reported that much of phosphatase substrate specificity, localization and activity is modulated by the interaction with scaffold/regulatory proteins that target them to specific locations (Roy and Cyert, 2009; Sacco et al, 2012b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatase-substrate interaction is weak and transient, thus it is unlikely that substrates can be identified by co-immunoprecipitation. In fact none of the interactors identified in the affinity purification experiments are among the validated substrates annotated in the HUPHO and DEPOD databases (Li et al, 2013; Liberti et al, 2013). It has been reported that much of phosphatase substrate specificity, localization and activity is modulated by the interaction with scaffold/regulatory proteins that target them to specific locations (Roy and Cyert, 2009; Sacco et al, 2012b).…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence accumulated over the past decades have indicated that this enzyme class plays an important regulatory role and that the deregulation of the concentration or activity of specific phosphatases correlate with a variety of human disorders (Wera and Hemmings, 1995; Tonks, 2006). Notably, approximately 40% of protein phosphatases are implicated in tumor development, highlighting the central role of this enzyme group in growth regulation and identifying some members of this enzyme class as promising therapeutic targets (Julien et al, 2011; Liberti et al, 2013). One of the problems in the characterization, on a large scale, of the functional role of members of the phosphatase family is the lack of a simple, robust, method to identify physiologically relevant substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The Human Phosphatase Portal (HuPho) [38] reports 135 protein phosphatases of which 107 are Protein Tyrosine Phosphatases (PTPs). The remaining 28 S/T phosphatases consist of two families, Metal Dependent Protein Phosphatases (PPMs or PP2Cs) and Phosphoserine Protein Phosphatases (PPPs).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatome of Lm has 172 phosphatases, while its kinome has 199 kinases [15], Gl has a phosphatome size of 151 phosphatases and its kinome consists of 278 kinases (Table 1). Human phosphatome has 199 proteins consisting of phosphatase domain [28]. There was a variation in apicomplexan phosphatomes size between different genera.…”
Section: Resultsmentioning
confidence: 99%
“…Eh has the highest percentage of phosphatases followed by Lm and Cp . The percentage of phosphatome in Hs is 0.6% of its proteome (Fig 1) [5, 28], which is much less than the selected parasites phosphatomes, indicating that vertebrates have various other mechanisms for the regulation of proteins but in protozoan parasites phosphorylation is an integral mechanism for protein regulation.…”
Section: Resultsmentioning
confidence: 99%